Kampanye Sosial Istana Belajar Anak Banten dalam Pembangunan Pendidikan di Era Digital - Tri Susanto; Leonard Dharmawan; La Dono; Irvan Roberto (Institut Pertanian Bogor, 2019)
Social campaigns are carried out to increase public awareness and behavior of various issues faced by a country. The development of the digital era now demands that campaigns be enjoyed and seen through online media. One of the social campaign activities was the Banten Children's Learning Palace (ISBANBAN), which involved young Bantenese in contributing to education in the area by using new media. This study aims to find out and describe the ISBANBAN social campaign communication strategy with the social marketing communication approach. This research is a qualitative research with a case study strategy that takes campaign activities through new media. The main data obtained through in-depth interviews and observations. The research findings provide an overview of the social marketing communication strategy carried out by ISBANBAN that connects offline interactions, namely teaching activities in remote Banten with online interaction, namely social media as the main channel in social marketing that aims to build brand awareness for donations, through new media information that gives more broad so it is expected to reach further adopter target targets. Target adopters of multiplayer donations that not only contribute funds but also energy and thought in an effort to advance education in remote Banten.